Environmental effects of the African Continental Free Trade Agreement: A computable general equilibrium model approach - Marta Bengoa; Somya Mathur; Badri Narayanan; Hanna C. Norberg (Journal of African Trade, 2021)
Growth and development in middle- and low-income countries often come at an environmental cost, but is that trade-off always necessary? This study uses a computable general equilibrium model to estimate the macroeconomic and environmental impact of the world's most significant plurilateral trade agreement, the African Continental Free Trade Agreement (AfCFTA). We build a novel dataset using the Global Trade Analysis Project data, which allows us to estimate the effect on emissions of carbon dioxide (CO2), non-CO2, and other pollutants. In terms of macroeconomic impact, African nations benefit from gross domestic product growth by 1.2% and employment by 2.1%, with less developed economies, such as Togo and Benin, obtaining the largest macroeconomic gains from trade liberalization. On aggregate, we estimate that the agreement will lead to a marginal, 0.3% increase in CO2 emissions, a 19.6% increase in non-CO2 greenhouse gas emissions, and a 21.5% decline in air pollutants. We find considerable heterogeneity across countries. For Nigeria, the rest of Central Africa, and South-Central Africa, the AfCFTA is expected to reduce emissions, while in Ethiopia, Cameroon, and Burkina Faso, estimations show an increase. Transit countries connected to large ports, such as Togo and Benin, are most negatively impacted. We conclude that while the AfCFTA implementation is expected to lead to notable improvements in air quality by reducing air pollutants, the resulting increase in climate-related emissions may require member countries to make concerted efforts to deal with the adverse effects.
Keywords: 330; Trade; environment; AfCFTA; CO2; non-CO2; greenhouse gas